The Lateral and Directional Stability Behavior for Two Aircraft Models - Shamsudin, Syariful Syafiq; Basuno, Bambang; Firdaus, Muhammed; Md Arifin, Latifah; Asmuin, Nor Zelawati (Progress in Aerospace and Aviation Technology, 2022)
The current study looks at flight behavior in lateral and directional motion. The investigation involves setting up the aircraft under an equilibrium condition with a small disturbance applied to it. Plotting the side slip angle, roll angle, and yaw angle with respect to time in the presence of disturbances can be used to investigate flight behavior in lateral and directional motion. Here the disturbance can be simulated by the movement of the aileron or rudder, in which these two control surfaces can be designed to move in a single impulse or multiple impulse disturbance mode. These two disturbance modes are used on the Beechcraft 99 and Cessna T37 aircraft. Both impulse disturbance models are used for the aileron and the rudder. However, in the current work, the Beechcraft 99 receives a single impulse, whereas the Cessna T37 receives multiple impulses. The implementation of such disturbances found that the Beechcraft 99 represented the aircraft that would be able to go back to its initial condition in response to a single impulse disturbance mode while the Cessna T37 aircraft requires a little more time to return to its original yaw angle. Following the implementation of these two types of disturbances, it was discovered that each aircraft has the ability to return to its initial condition, but at varying times to reach its steady state solution.